BioMEMS Science and Engineering Perspectives - Badilescu, Simona (Taylor & Francis, 2011)
Written to cover often overlooked areas in the field of bioMEMS, this volume bridges topics related to biomolecules and complex biological entities with those directly related to the design, fabrication, and characterization of the devices. Unlike other references, this text aids with the fundamental physicochemical understanding of biological processes relevant to the performance of various biosensing devices. Accessible to seniors and graduate students enrolled in engineering programs, the book includes problems in each chapter as well as case studies to provide real-life examples.